Effect of Graphene Oxide on the Performance of Fly Ash Concrete Exposed to Ambient Temperature - Maizuar; Akbar, Said Jalalul; Jalil, Abdul; Arfiandi, Joni (Salehan Institute of Higher Education, 2025)
The rising global temperatures due to climate change are accelerating concrete deterioration by shortening its service life, which subsequently increases maintenance costs. Therefore, the objective of this investigation is to analyze the graphene oxide (GO) effect on the mechanical characteristics and microstructural properties of fly ash (FA) concrete exposed to ambient temperatures. Concrete specimens were created by employing GO from 0.01% to 0.05% by weight of cement and cured using two distinct methods. These include standard curing in immersed water and for 7 days followed by ambient exposure. The mechanical test showed that GO significantly enhanced compressive strength, with 0.04% GO observed to have increased strength by approximately 16% at 28 days. However, exposure to ambient conditions led to decreased compressive and flexural strength and increased mass loss. The microstructural analysis also showed that ambient-exposed concrete exhibited higher porosity and incomplete hydration. The results showed that the addition of GO enhanced durability by refining the microstructure, reducing porosity, and enhancing thermal stability. Thermal analysis also confirmed that GO minimized moisture loss and improved thermal resistance. Furthermore, Fourier Transform Infrared Spectroscopy (FTIR) validated the improvement in bonding for the GO-FA concrete. These results showed that GO could mitigate the adverse effects of environmental exposure, leading to its identification as an advantageous additive to increase the long-term durability and concrete performance in different temperature conditions.